TELAAH FILOSOFIS ATAS ARSITEKTUR DIGITAL Kasus Studi Arsitektur Digital Neo-Nusantara di Ibu Kota Negara (IKN) - Rudyanto Soesilo (Universitas Katolik Soegijapranata, 2022)
All aspects of life cannot escape the development of the times with the last phenomenon being the influence of the development of the digital world which is called the process of